THE EFFECTIVENESS OF USING ORAL PAIR WORK TECHNIQUE IN TEACHING SPEAKING AT DEC (DYNAMIC ENGLISH COURSE) PARE KEDIRI - Mufidah, Izzatul (Jurnal Pendidikan Bahasa Inggris Proficiency, 2019)
This study aims at knowing how effectiveness of oral pair work technique in teaching speaking at DEC. The research design which is used in this research was descriptive quantitative experimental with two groups of experimental class and control class. The subjects of this research were the holiday program of SMA A and SMA B. The instruments used were post-test. The data gotten were statistically computed by SPSS.The result reveals that experimental group outperformed the control group with significance value 0.2% or 0.002 at either 5% or 1% significancy level. So, it can be concluded that teaching speaking by using oral pair work technique is effective.